THE EFFECT OF SERVICE QUALITY AND COMPLAINT HANDLING ON COMMUNITY SATISFACTION OF PUULORO VILLAGE OFFICE, SAMPARA DISTRICT, KONAWE REGENCY - Beemu, Sardin; Muthalib, Abdul Azis; Supriaddin, Nofal; Hakim, Abdul (IJMA (Indonesian Journal of Management and Accounting), 2024)
Good quality of public services and effective complaint handling are important factors in increasing community satisfaction with the services provided by the village government. However, there is still a gap in understanding how these two variables affect the level of community satisfaction in rural areas, especially in the Puuloro Village Office, Sampara District, Konawe Regency. The lack of research specifically examining the relationship between service quality and complaint handling at the village level suggests that there are gaps in the literature that need to be filled. This study uses a quantitative approach with a survey method and Slovin sampling technique, involving 86 respondents to test the influence of these two variables on community satisfaction. The findings of this study show that the quality of service and handling of complaints simultaneously and partially has a positive and significant effect on community satisfaction. Practically, the results of this study provide recommendations for village governments in improving the quality of service and responsiveness to community complaints, which ultimately contributes to increasing community trust and loyalty to government agencies. This research has limitations on the scope of objects limited to one village, so further research is recommended to expand the variables and objects of research.